Barbara McClintock - Cullen, J. Heather (Philadelphia : Chelsea House Publishers, 2003)
Presents the life and career of the geneticist who in 1983 was awarded the Nobel Prize for her study of maize cells
A life in science -- Family life -- Learning lessons at Cornell -- Is this a career? -- Free to do research -- Jumping genes at Cold Spring Harbor -- In the spotlight -- A legacy for the future
Includes bibliographical references (p. 113)
Keywords: McClintock, Barbara, -- 1902- -- Juvenile literature; McClintock, Barbara, -- 1902-; Women geneticists -- United States -- Biography -- Juvenile literature